RELEASE OF VASOPRESSIN DURING SUPPRESSION OF OESTROUS CYCLE IN RAT BY ZOLADEX AND HYPOVOLEMIC CHALLENGE - Kundi, Salma Aslam; Wazir, Saleem; Afzal, Saleem; Afzal, Naeema; Qayum, Iftikhar; Forsling, Mary L. (Journal of Ayub Medical College Abbottabad, 2005)
Background: The vasopressin (AVP) response to hypovolemia has been compared in intact and chemically castrated rats. This functional ovariectomy was done to confirm the findings in surgical ovariectomy of how gonadal steroids modulate the release of AVP under hypo-volemic challenge. Methods: Twenty female Sprague Dawley rats were checked for oestrous over two consecutive cycles. The ten control rats were given sub-cutaneous puncture only whereas the experimental were given Zoladex implant. On the fifteenth day all the rats were given intra-peitoneal injection of poly-ehylene glycol. All the rats were de-capitated after an hour. Results: The uterine weight was significantly decreased in experimental group. The plasma AVP level was also significantly decreased in the experimental group. The pituitary AVP level was significantly increased in the experimental group. Conclusion: The chemical castration effected the AVP secretion, this proves that the sex steroids modulate the release of AVP secretion inspite of hypo-volemic challenge. Keywords: Zoladex, Hypovolemia, Vasopressin